The Importance of Hope to Resilience in Criminal Justice Diversion Programs - Ozturk, Burcu (Criminology, criminal justice, law & society, 2022)
The United States has the highest levels of incarceration in the world, and finding ways to address this ever-growing concern has value both to system-involved individuals and broader society. "Diversion" programs are a pre-trial option that provides rehabilitation and personal development as alternatives to incarceration. Hope is an asset to coping with adversity, and studies have revealed that people who have lower levels of hope are at greater risk of becoming involved in the criminal justice system. One characteristic linked to success in navigating diversion programs is psychological resilience, with hope theory suggesting a hopeful mindset is an antecedent of that resilience. The current study (N = 52) evaluated this theory by testing a model of hope as a driver of resilience. Participants were receiving various diversion-related services in the Heartland of the United States. Participant surveys included established measures of both hope and resilience. First, item scores' principal component analysis (PCA) revealed that hope and resilience operated as unique psychological constructs within the sample. A subsequent path model analysis of hope as a predictor of resilience indicated that, as theorized, hope accounted for 17.2% of the variance in resilience across both race and gender. The results support that hope is essential to psychological resilience among diversion clients. The results suggest that future research into hope theory-based interventions with diversion clients is worthwhile.